INTERNAL CONTROL SYSTEMS AND RISK MANAGEMENT IN THE LIFE AND HEALTH INSURANCE INDUSTRY: CURRENT ISSUES - André, Paul; Coté, Diane; Morissette, Raymond (Assurances)

(untitled) (HEC Montréal, 1999)
The increased used of derivative products by both financial and non-financial institutions and recent shortcomings in the management and control of these products which had severe economic consequences for these companies and numerous investors, continue to demonstrate the need for enhanced standards of control over risks undertaken by all active participants in capital markets. The objective of this paper is to show how good internal control systems, with a particular emphasis on the internal audit and compliance functions within such systems, mitigate important types of risks and must be integrated within an integrated risk management framework. Our focus is on the Life and Health lnsurance industry in Canada. We will draw attention to the regulatory environment and recent regulatory and supervisory developments with respect to risk management practice. We conclude with a discussion of two recent and useful management tools that can be used in a global risk management practice: Controland Risk Self-Assessment (CRSA) and the Balanced Scorecard approach including a Risk Management perspective.